Nasal colonization with Staphylococcus aureus in individuals with HIV/ AIDS attended in a Brazilian Teaching Hospital - Lilian Andreia Fleck Reinato; Daiana Patrícia Marchetti Pio; Letícia Pimenta Lopes; Fernanda Maria Vieira Pereira; Ana Elisa Ricci Lopes; Elucir Gir (Universidade de São Paulo, 2013)
OBJECTIVE: to evaluate the prevalence of nasal colonization with Staphylococcus aureus in individuals with HIV/AIDS under inpatient treatment in a teaching hospital in the state of São Paulo (Brazil). METHOD: a cross-sectional study undertaken in two units specialized in attending people living with HIV/AIDS, in the period August 2011 - July 2012. Socio-demographic and clinical data was collected through individual interviews and from the medical records; samples of nasal secretion were collected with Stuart swabs on the first day of inpatient treatment. Ethical aspects were respected. RESULT: of the 229 individuals with HIV/AIDS hospitalized in this period, 169 participated in the study, with Staphylococcus aureus being identified in the culture tests of 46 (27.2%) of the individuals, resistance to oxacillin being evidenced in 10 (21.8%) participants. CONCLUSION: the results of the research indicate that the prevalence of colonization with Staphylococcus aureus in individuals with HIV/AIDS in the specialized units was considered relevant, possibly contributing to future investigations and, moreover, to the implementation of measures to prevent and control this pathogen in this population.